The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1007/bf01116238
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic fluorescence studies on saccharide binding toArtocarpus integrifolialectin

Abstract: The combining region of Artocarpus integrifolia lectin has been studied by using the ligand-induced changes in the fluorescence of the lectin. The saccharide binding properties of the lectin show that C-1, C-2, C-4, and C-6 hydroxyl groups of D-galactose are important loci for sugar binding. The alpha-anomer of galactose binds more strongly than its beta-counterpart. Inversion in the configuration at C-4 as in glucose results in a loss of binding to the lectin. The C-6 hydroxyl group is also presumably involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…Lectin protein from jackfruit seeds (jacalin) binds with a primary specificity to non-and monosialylated core 1 (Gal␤-1,3GalNAc-␣) O-linked carbohydrate (26,42,48,53). To determine if SIVmac239 is sensitive to jacalin, the replication of SIVmac239 was assayed at a low multiplicity of infection under conditions of a spreading infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lectin protein from jackfruit seeds (jacalin) binds with a primary specificity to non-and monosialylated core 1 (Gal␤-1,3GalNAc-␣) O-linked carbohydrate (26,42,48,53). To determine if SIVmac239 is sensitive to jacalin, the replication of SIVmac239 was assayed at a low multiplicity of infection under conditions of a spreading infection.…”
Section: Resultsmentioning
confidence: 99%
“…It remains possible that HIV-1 gp120 is modified with mucin-type O-linked carbohydrate to which jacalin and PNA do not bind. Jacalin binds the Tn antigen, core 1, and monosialylated core 1 mucin-type carbohydrate (26,42,48,53). PNA binds to nonsialylated core 1 carbohydrate (31,35,47,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbohydrate-binding specificity of jacalin has been studied intensively since the discovery of its specific interaction with IgA1 [8] and the Thomsen-Friedenreich or T-antigen disaccharide Galβ1,3GalNAc [9]. Measurements of the intrinsic fluorescence of excited jacalin in the presence of various sugars indicated that -galactose, β-Met-Gal and 2-deoxy-α--galactose are the most potent inhibitors of the lectin [10]. Hapten inhibition of the agglutination of IgA1-coated latex particles by simple sugars and sugar derivatives demonstrated further that the inhiAbbreviations used : Heltuba, Helianthus tuberosus agglutinin ; HBS, Hepes-buffered saline ; MPA, Maclura pomifera agglutinin ; Neu5Ac, N-acetylneuraminic acid ; MurNAc, N-acetylmuramic acid ; SPR, surface plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%
“…The jacalinglycoprotein interaction was found to be sugar specific as it could be inhibited in the presence of 0.1M galactose. Investigations of jacalin's ligand specificity revealed its high affinty for ec-galactopyranosides and particularly for the T-antigen with the structure, 1-J~-D-galactopyra nosyl-3-(o~-2-acetamido-2-deoxygalactopyranoside) (13,14). Jacalin recognizes the T-antigenic structure on glycoproteins even when substituted with a terminal sialic acid residue (15).…”
Section: Discussionmentioning
confidence: 99%